Genre Analysis Of Descriptive Text Written By Students Of SMP Negeri 3 Teras In 2012-2013 Academic Year - Maulana, Fery Ardiansah; , Aryati Prasetyarini, M.Pd; , Dra. Dwi Haryanti, M.Hum (2013)
The objectives of the study are: (1) to describe the genre of descriptive text written by the students of SMP N 3 Teras, and (2) to identify the problems faced by the student in writing descriptive text. The type of the study is a qualitative research. The object of this study is descriptive text written by SMP Negeri 3 Teras. In collecting data, the writer uses elicitation and documentation. There are three steps to collect data, namely: the writer gets the data of English composition made by the students from the teacher, reads the text written by students accurately, and identifying data which have mistakes in their genre. The collected data are analyzed by using theory of genre written in Readings on English Text by Halliday and Hasan theory. The result of the study shows that the students of SMP Negeri 3 Terasha ve low ability mastering in English, especially in writing. The writer finds there are some mistakes and error made by the students. From 6 numbers of data, only two students can complete the element of generic structure in descriptive text. But all of them are out of topic. Four another students can't complete the elements of generic structure. One of them can't make identification, two of them can't make description and the last one student can't make identification and description. The problems that faced by the students are: (1) the students do not understand the generic structure elements of descriptive text, (2) the student does not understand the purpose of descriptive text, (3) the students can't write well in English.